SUMMARY OF COLONOSCOPY RESULTS IN VERY ELDERLY PATIENTS AT THONG NHAT HOSPITAL - Thị Thanh Loan, Nguyễn; Thiên Như Ý, Nguyễn; Việt Trung, Huỳnh (Journal of Health and Aging, 2025)
Colonoscopy is an important procedure for diagnosing and treating lower gastrointestinal diseases. However, performing colonoscopy in very elderly patients poses many challenges, particularly in the quality of bowel preparation and the risk of complications. Objective: To describe the characteristics of colonoscopy in patients aged ≥ 80. Methods: A cross-sectional study was conducted on 254 patients aged ≥ 80 who underwent colonoscopy at Thong Nhat Hospital. Results: The mean age was 84,7 ± 3,16. No cases of perforation or bleeding related to colonoscopy were reported. 32,7% procedures were performed with sedation. The main reasons for incomplete colonoscopies were poor bowel preparation (52,6%) and intolerable pain (39,5%). Polyps were the most commonly detected lesions (48,6%), with the majority having ≥ 3 polyps and measuring
Keywords: colonoscopy; very elderly patient